Pendampingan Operasional Industri di Mekar Jaya - Widjajani, Nia; Nurjaman, Risris (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2020)
Industry is an activity that is carried out from one other activity to the goal of the purpose of to reduce goods or services. The resulting goods can certainly be valuable to consumers. One feature of the goods is acceptable on the market and can provide a profit. The implementation of small industrial operations obviously does not extend the enterprise above. Various resource limitations must be faced by the company. However, with good circumlocution is expected although slowly but can develop well. One of the growing companies is the home industry processed snacks. Revenue is needed to strengthen managerial so that the target development within the company.